IMPACTS OF SOLAR RADIATION MANAGEMENT ON EVAPORATIVE HEAT FLUX OVER WEST AFRICA - Adenuga, Kayode P; Ojo, Olusola Samuel; O. R., Obasi-Oma; Oloniyo, Olumuyiwa; Adeyemi, Babatunde; Agele, Samuel (Journal of Science, Technology and Innovation Research, 2026)
This study investigates the impacts of solar radiation management through stratospheric aerosol injection (SAI) on the spatial variability of evaporative heat flux across West Africa. Evaporative heat flux represents a key component of land and atmosphere energy exchange and plays a critical role in regulating regional hydrological processes and surface temperature. Monthly evaporative heat flux data from the ERA5 reanalysis dataset were used as an observational reference for the historical period 1980–2014. Climate projections were obtained from an ensemble of fifteen global climate models participating in the Coupled Model Intercomparison Project Phase 6 (CMIP6). Future climate conditions were analysed under two greenhouse-gas emission scenarios, SSP2-4.5 and SSP5-8.5, for the period 2035–2069. To evaluate the potential effects of solar geoengineering, the ARISE-SAI-1.5 experiment was incorporated. All datasets were re-gridded to a common spatial resolution of 0.25° × 0.25° using bilinear interpolation implemented through Climate Data Operators. Model performance was evaluated through grid-based bias analysis using ERA5 observations. Results reveal strong spatial gradients in evaporative heat flux across West Africa, with values exceeding 80 W m-² in humid coastal regions and falling below 40 W m-² across the Sahel. The CMIP6 historical simulations reproduce these spatial patterns reasonably well, with bias values generally ranging between −10 and +10 W m-². Under future emission scenarios, moderate increases in evaporative heat flux are projected across several parts of the region. However, the introduction of SAI results in a reduction of evaporative heat flux across large portions of West Africa, with changes typically ranging between −25 and 10 W m-². These results suggest that solar radiation management could influence land and atmosphere energy exchanges and potentially moderate extreme climate conditions in climate-sensitive regions. The study provides new insights into the regional implications of solar geoengineering and highlights the need for further evaluation of SAI alongside conventional mitigation and adaptation strategies in West Africa.